Coordinating physiotherapy care for persons with haemophilia. Issue 6 (7th September 2021) - Timmer, Merel A.; Blokzijl, Johan; Schutgens, Roger E. G.; Veenhof, Cindy; Pisters, Martijn F.
Abstract: Introduction: Physiotherapy is highly recommended for persons with haemophilia (PWH), to regain functioning after bleeding and to maintain functioning when dealing with haemophilic arthropathy. However, many PWH live too far from their Haemophilia Comprehensive Care Centre (HCCC) to receive regular treatment at their HCCC. Physiotherapists in primary care may have limited experience with a rare disease like haemophilia. Aim: To explore experiences of stakeholders with primary care physiotherapy for PWH and develop recommendations to optimize physiotherapy care coordination. Methods: A RAND approach was used, consisting of a Delphi procedure with e‐mailed questionnaires and a consensus meeting. Included stakeholders were PWH, physiotherapists from HCCC's and primary care physiotherapists. HCCC physiotherapists approached patients from their centre and primary care physiotherapists from their network to fill in the questionnaires. Purposive sampling was used to select participants from the survey sample for the consensus meeting. Results: Ninety‐six primary care physiotherapists, 54 PWH and eight HCCC physiotherapists completed the questionnaire. Subsequently, four PWH, three primary care physiotherapists and four HCCC physiotherapists participated in the consensus meeting. The questionnaires yielded 33 recommendations, merged into a final list of 20 recommendations based on the consensus meeting. The final rank‐order consists of 13 recommendations prioritized by at least one stakeholder. Conclusion: Commitment to a formal network is considered not feasible for a rare disease like haemophilia. Development of a practice guideline, easy‐accessible information and contact details, two‐way and open communication between HCCC and primary care and criteria to refer back to the HCCC are recommended.